Risk reduction at oil and gas industry using methods of synthesis of flame retardant coatings (Nexo Revista Científica, 2021)
This article studies the influence of zeolites with microencapsulated water on flame retardant efficiency of intumescent compositions with epoxy resins under conditions of hydrocarbon jet fire. The flame retardant efficiency has been simulated and estimated using regression analysis. The synthesis of ablation/desorption flame retardant coatings is described.